Numerical investigation of the behaviour of jets in a wave environment. Issue 4 (6th June 2020) - De Padova, Diana; Mossa, Michele; Sibilla, Stefano
ABSTRACT: This paper presents the application of a weakly compressible smoothed particle hydrodynamics model to study plane jets propagating into a still ambient and into a flow field of regular waves. The present study includes a comparative investigation of the main ﬂuid mechanics characteristics in cases of jet discharged either in still water or transversally to regular wave trains characterized by different periods. Concerning jets in a wave environment, the present study shows the existence of the following three different regions of the jet-wave ﬁeld starting from the nozzle in the intermediate water: the nearest region to the nozzle where the jet motion dominates the wave motion; the intermediate region, where the horizontal velocity component of wave motion dominates the jet centreline velocity decay; and the nearest region to the free surface where the wave period dominates the jet motion. The present study shows the differences found numerically between each ﬂow region.